Eugene O’Neill’s Long Day's Journey into Night as an Autobiographical Play - الفرج، لينا; خلف، إلياس مصطفى (جامعة البعث, 2017)
This research aims at presenting Eugene O’Neill’s much distinguished play Long Day’s Journey into Night as an autobiographical work by reason of the many similarities between his own life and his fictional work. I have chosen this topic because I believe that his personal life and suffering have greatly influenced his writing. In this play in particular, his biography enables us to appreciate it and provides us with a better understanding of its themes. His reliance upon his personal experiences makes his play powerful, clear, profound, faithful and honest. The play’s strength lies in the family portrayed- the Tyrones or the O’Neills. There are a father, a mother, and two sons in the play. The father, James Tyrone, is a drunkard and poor actor. Mary Tyrone is a morphine addicted mother. The elder brother, Jamie, is cynical and alcoholic, and the younger son, Edmund, is a physically sick boy. Long Day's Journey into Night, which gives title and course to the play, is a different journey during which the characters show their personal psychological needs. For the father, it is a sad journey down the false road, away from his previous success. For the mother, it is a tragic journey into the fog of drugs and dream. For Jamie, it is a desperate journey into the dark of sardonicism and hopelessness. While for Edmund it is a journey after night.
يهدف هذا البحث إلى تقديم أكثر مسرحيات يوجين أونيل تميزا "رحلة يوم طويل خلال الليل" بوصفها سيرة ذاتية للكاتب آخذين بالحسبان العديد من أوجه التشابه بين حياة أونيل الشخصية وعمله الأدبي هذا. اخترت هذا الموضوع لأنني أعتقد أن حياته الشخصية ومعاناته أثرتا كثيرا في كتاباته، فسيرة حياته في هذه المسرحية تحديدا تمكننا من تقييمها وتعطينا فهما أفضل لأفكارها. إن اعتماده على تجاربه الشخصية جعل مسرحيته هذه عميقة وصادقة، إذ تكمن عظمة المسرحية في تصويره أسرة تايرون (أسرة أونيل). تتضمن المسرحية شخصيات الأب والأم وابنين. الأب، جيمس تايرون، ممثل بخيل مدمن على الخمرة، وماري تايرون أم مدمنة على المورفين، أما الشقيق الكبير، جيمي، فهو شاب ساخر وسكير، والابن الصغير، إدموند، شاب مريض. "رحلة يوم طويل خلال الليل" عنوان المسرحية الذي يحدد مسارها هي رحلة مختلفة إذ تظهر الشخصيات احتياجاتها النفسية الخاصة، فالرحلة بالنسبة إلى الأب رحلة شقاء في الطريق الخطأ تاركا نجاحه السابق، أما بالنسبة إلى الأم فهي رحلة مأساوية إلى ضبابية الحلم والمخدر، وهذه الرحلة كانت بالنسبة إلى جيمي رحلة يائسة في ظلام السخرية، لكنها كانت رحلة تنوير بالنسبة لإدموند.
Keywords: الأدب الإنجليزي -- الشخصيات المسرحية -- السيرة الذاتية -- أونيل، يوجين، ت. 1953 م